The Concept Of Female Body In Shallow Hal Movie - Widya Nirmalawati; Sulasih Nurhayati (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
The concept of the human body has existed since ancient Greece. The Greece philosopher halted from Plato, followers, and thinkers have different concepts about the body. The human body is so important that many discussion related to the body has always been an endless debate. This kind of debate is also depicted in Shallow Hal (SH) movie produced in 2001. The film shows the story of a man named Hal (Jack Black) and Mauricio (Jason Alexander). Both men have an interest in women who are slender and beautiful. Through the issue of the body by using the discourse analysis approach and Michel Foucault's theories of power, this study analyzes how the concept of the female body as a form of discipline is represented in the film. From the data in analysis, it is found that the beautiful concept reflected in the film shows that woman can be said to be beautiful if she has the standards prevailing in society; that is she must be slim, has big breasts, long legs, and a perfect body proportions. This concept is often presented by the media which eventually becomes the true standard of how the woman’s body should be. Hence, it can be said that the media plays a role in shaping the discourse how the concept of beauty of the acceptable female body. Media, in this case, is the main stakeholder in winning the discourse